Effect of hail protection nets on apple scab in 'Royal Gala' and 'Fuji' apple cultivars - Agostineto L.* (2012)
In commercial apple orchards in Southern Brazil, it is common to avoid hail damage by covering the trees with nets. However, this technology can affect the epidemiology of some apple diseases, specially the apple scab (AS). This study was carried out to assess the effects of both black and white hail netting on the temporal dynamics of AS disease in a commercial 'Royal Gala' and 'Fuji' apple orchard in a high-altitude region of Southern Brazil during two growing seasons. Apple trees on M9 rootstock, trained to a slender spindles and with a spacing of 3.5 m × 0.8 m, were left uncovered (control condition) or covered with black or white hail netting. The incidence and severity of AS were quantified biweekly from October to February by evaluating 100 leaves distributed randomly on four medium-height branches per plant with 12 replications. Disease progress curves were constructed and the epidemics were compared by four epidemiological measures: the beginning of symptom appearance (BSA), the time to reach the maximum disease intensity (TRMDI), the maximum value of disease severity (Y max), and the area under the disease progress curve (AUDPC). The highest intensity of AS was observed in the plants under the black hail netting. Reductions in BSA and TRMDI and increases in Y max and AUDPC by the hail net were found in both 'Royal Gala' and 'Fuji' cultivars and growing seasons. Differences between white hail netting and control condition on BSA and TRMDI for AS were found in both cultivars and growing seasons. However, no differences between white hail netting and control condition on AUDPC for AS were found in both cultivars and growing seasons, except for 'Fuji' cultivar in 2004/05 growing season. The results of the study showed that the hail protection system using black hail netting is susceptible to increase the intensity of apple scab more than white hail netting. © 2012 Elsevier Ltd.